Ixochymostatin, a trypsin inhibitor-like (TIL) protein from Ixodes scapularis, inhibits chymase and impairs vascular permeability - Martins, Larissa Almeida; Berger, Markus; Kotál, Jan; Lu, Stephen; Sousa-Paula, Lucas C; Smith, Brian J; Zhang, Yixiang; Andersen, John F; Tirloni, Lucas (International journal of biological macromolecules, 2025)
Ticks obtain a blood meal by lacerating small blood vessels and ingesting the blood that flows to the feeding site, which triggers various host responses. However, ticks face the challenge of wound healing, a process involving hemostasis, inflammation, cell proliferation and migration, and remodeling, hindering blood acquisition. To overcome these obstacles, tick salivary glands produce an array of bioactive molecules. Here, we characterize ixochymostatin, an Ixodes scapularis protein belonging to the trypsin inhibitor-like (TIL) family. It is expressed in multiple developmental stages and in tick salivary glands and acts as a slow and tight-binding inhibitor of chymase, cathepsin G, and chymotrypsin. Predictions for the tertiary structure complex between ixochymostatin and chymase suggest a direct interaction between the inhibitor reactive site loop and protease active sites. In vitro, ixochymostatin protects the endothelial cell barrier against chymase degrading action, decreasing cell permeability. In vivo, it reduces vascular permeability induced by chymase and compound 48/80, a mast cell degranulator agonist, in a mouse model. Additionally, ixochymostatin inhibits the chymase-dependent generation of vasoconstrictor peptides. Antibodies against ixochymostatin neutralize its inhibitory properties, with epitope mapping identifying potential neutralization regions. Ixochymostatin emerges as a novel tick protein modulating host responses against tick feeding, facilitating blood acquisition.
Keywords: Ixodes; proteiny členovců; Humans; Inhibitor; Trypsin inhibitor-like; kapilární permeabilita; Ixodes scapularis; Chymase; Salivary Glands; klíště; Chymases; lidé; zvířata; myši; Arthropod Proteins; Capillary Permeability; chymasy; Mice; Trypsin Inhibitors; Amino Acid Sequence; slinné žlázy; inhibitory trypsinu; Animals; Tick saliva; sekvence aminokyselin